Transformation of Young People’s Attitude Toward Work in the Old Industrial Region: Ontogenetic Aspect - Pavlov, Boris Sergeyevich (Economy of Regions, 2015)
The article emphasizes that for the countries facing the crisis of natural reproduction of human resources, the improvement of their quality is the only option for economic growth policy. According to the author’s opinion, the Achilles heel of the modern system of the labor potential reproduction of society (at all its territorial and settlement levels), of the development and the utilization of human resources is a failure in the field of working education for Russian young generations at the stage of general education and professional socialization. Working activity for the developing child’s personality is necessary, irreplaceable attribute of socialization. The article presents the idea that early adult students (students in the later years of high school or the early years of higher education) should participate in adequate socially useful work, which should not be limited only to the pedagogic issues. As the young people get older, not only the potential ability to work should grow. The author believes that child labor (and the following working education) in modern Russia is reduced to the rank of "outside the pedagogical law". On the basis of statistical data, the author demonstrates that the socio-economic behavior of the overwhelming majority of the early adult students of the Ural region are mainly geard toward a leisurely consumerist lifestyle. In particular, the attention is focused on the development and strengthening of the selfish behavior of students, ignoring the limited financial resources of their parents, sponsoring their studies at the institute of higher education. The particular attention is paid to the issues of the social and settlement assimilation of the young people in the Ural region. It is shown that the village youth learn the deviant subculture of urban youth, which has a significant impact on the process of destabilization of the basis of rural way of life. The findings and suggestions of the article are based on the results of a number of comprehensive sociological research conducted in 2003-2014 in urban and rural areas of the Ural region under the supervision and with the direct participation of the author.